ATTRACTIONS OF KINANTAN WILDLIFE AND CULTURAL PARK BUKITTINGGI CITY, WEST SUMATRA PROVINCE - Arsyifa Indriana; Andri Sulistyani (Fakultas Ilmu Sosial dan Ilmu Politik Universitas Riau, 2022)
Kinantan Wildlife and Culture Park is one of the historical relics that has become one of the tourist attractions in Bukittinggi. The zoo was built by the Dutch East Indies government in the 1900s. The purpose of the study was to find out the tourist attractions of TMSBK and the efforts of managers in attracting visits to TMSBK. Tourist attractions must meet the conditions for the development of the area, namely what to see, what to do, what to buy, what to arrived, what to stay. A zoo is a place in the form of a park or green open space useful for demonstrating animals to the public and which is regulated as an ex-situ conservation institution. The method in the study is descriptive qualitative. As a result of the interview, Kinantan Wildlife and Cultural Park is located in the Bukittinggi Upper Market Fort which has attractions including the Limpapeh bridge and fort De Kock left over from the Dutch era. Management efforts to increase visits by means of promotion through social media and improving existing facilities. The management and the Bukittinggi City Government are working together in improving the Bukittinggi Kinantan Wildlife and Cultural Park to improve local revenue the Bukittinggi City. Keywords : Attraction, Social Media, Wildlife Park and Kinantan Culture